KONSEP METAFISIKA MUHAMMAD IQBAL - Ali Kartawinata (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2016)
Muhammad Iqbal’s ideas of metaphysics emphasized that there is source of other experiences above the normal level, which is referred to as intuition. This experience differs from mind and perception. Intuition entered into human being as reality which is not reached by mind and perception. Self-reality can be found through intuition method. From self-reality yielded by intuition, and then found material-reality. The essence of material world is the self, since self is life. Hereby, the essence of the world reality has always changed constantly and freely. The fact is not static. There are no two occurrences in the life of reality which are similar to one another. There are activities, actions, and movements which remain permanently. Thus, the essence of life is action and movement itself. This Paper tries to explore Muhammad Iqbal’s idea of metaphysics and how the intuition process in the end is able to explain about reality.